Penerapan Algoritma C5.0 Data Mining Untuk Mengetahui Pola Kepuasan Mahasiswa Terhadap Pelayanan Akademik - Agung Triayudi (Universitas Budi Darma, 2022)
Students are one of the important aspects in improving the quality of higher education. One of the services provided to students is academic services. Knowing the satisfaction of academic services to students for tertiary institutions is quite important. The process carried out to determine student satisfaction has several obstacles, such as the use of a special process to determine student satisfaction. Knowing the pattern of student satisfaction with academic services must be known. To find out the pattern of student satisfaction, it can be done by processing data based on the questionnaire data that has been done previously. Data mining is a process of processing data stored in data warehouses. Data mining performs large data processing with the aim of obtaining valuable information stored in the data set. The C5.0 algorithm is one of the algorithms in data mining that can help solve problems in data processing. The C5.0 algorithm gets results based on the decision tree, the results from the decision tree will later become a new rule or role. The results obtained from the research process are a rule or pattern that can be used to determine the attributes or services that cause dissatisfaction with academic services to students.